The determinants of administrative staff performance at Muyang Kute Regional General Hospital - Lefiana, Dilla; Siagian, Masryna; Hartono, Hartono (Buletin Kedokteran & Kesehatan Prima, 2025)
This study investigates the factors influencing the performance of administrative staff at Muyang Kute Regional General Hospital, a government-owned healthcare facility in Bener Meriah, Indonesia. Utilizing an analytical survey with a cross-sectional design, data were collected from 89 permanent administrative staff members through questionnaires and hospital documents. Bivariate analysis, using the chi-square test, revealed a significant relationship between incentive provision and employee performance (p<0.001), with adequate incentives correlating with good performance. Similarly, effective employee development significantly impacted performance (p<0.001), with effective development programs leading to better performance. However, work facility provision did not significantly influence performance (p=0.475). The findings highlight the critical role of incentives and employee development in enhancing administrative staff performance, suggesting that targeted interventions in these areas could improve service quality and patient satisfaction.